Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.15294/kreano.v13i2.38068
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rainbow Mathematics Card in TGT Learning For Increasing Mathematics Communication Ability

Abstract: Mathematics communication, which includes writing, drawing, and expressing mathematics, is essential in learning mathematics. The teacher needs to design learning to develop the ability to communicate mathematically. Questions presented in the Rainbow Mathematics Card (RMC) allow participants to be educated to convey the ideas and concepts that become part of developing mathematics communication ability. The study aims to make mathematics communication ability TGT learning with RMC. A type study is a mixed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The purpose of learning mathematics is explicitly the importance of mathematical hard skills for students (Darwanto, 2019). Hard skill is the ability to master cognitive science (Fan et al, 2017;Kunanusorn, 2021;Sumarmo, 2014) and academic skills (Permendikbud, 2016;Sugianto et al, 2022) that students acquire through direct activities (Sopa et al, 2020;Wisshak & Hochholdinger, 2020). Therefore, it can be concluded that mathematical hard skills are students' ability to solve mathematical problems, manifested in direct activities in the learning process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of learning mathematics is explicitly the importance of mathematical hard skills for students (Darwanto, 2019). Hard skill is the ability to master cognitive science (Fan et al, 2017;Kunanusorn, 2021;Sumarmo, 2014) and academic skills (Permendikbud, 2016;Sugianto et al, 2022) that students acquire through direct activities (Sopa et al, 2020;Wisshak & Hochholdinger, 2020). Therefore, it can be concluded that mathematical hard skills are students' ability to solve mathematical problems, manifested in direct activities in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Student activity in the learning process can be seen when students can conclude mathematical problems. Furthermore, students will be able to conclude when using their mathematical hard skills, especially in the ability to think creatively (Masfingatin et al, 2020;Siburian et al, 2019), think logically (Triatmi & Setiawan, 2018;Wahyuddin et al, 2021), critical thinking (Changwong et al, 2018;, communication (Kamid et al, 2020;Sugianto et al, 2022), connection (Baiduri et al, 2020;Knuth, 2020;Rizki et al, 2022), the problem solving (Björn et al, 2019;Güner & Erbay, 2021;Rahmah et al, 2022), reasoning, (Kabael & Akin, 2018;Palinussa et al, 2021;Sterner et al, 2020) and understanding (Basir et al, 2020;Bossé et al, 2021;Minarni et al, 2016;Nurani et al, 2021). However, students can nott master all of these aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Technology is a design that creates a product and increases efficiency in all human activities. Technology is gradually changing people's lifestyles and mindsets, especially among teenagers Humaidi et al, 2022), especially in its use as a learning resource that can increase students' interest in learning (Effendi et al, 2022;Lei et al, 2021;Sugianto et al, 2022) Interest plays an important role in learning mathematics (Tafonao, 2018;Wicaksana, 2020). Students who are interested in learning are able to use higher cognitive processes to study, learn, and master the material presented to them (Leyva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is inefficient because the only means used are textbooks and students have to pay a lot of money to get them. One of the media that can help increase student interest in learning is by using social media Sugianto et al, 2022) Social media is a technology product that is often used to exchange information online. Social media is a type of online where users can easily participate, share and create content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation